Efeitos da radiação ionizante na qualidade do camarão branco do pacífico (litopenaeus vannamei) - Pereira, Ana Carla da Silva Caetano (2014)
The shrimp is a food well appreciated by consumers and represent important source of nutrients for the human diet. It is also a very perishable product that needs conservation treatments to maintain their freshness. Thus, the use of ionizing radiation, combined with cooling, may be a promising treatment for acting in disinfecting and increase its useful life. This study aimed to evaluate the effects of different doses of ionizing radiation and lifetimes of peeled shrimp (no cephalothorax and carapace) and headless (without the cephalothorax) when combined cooling. The first step was to analyze different doses of ionizing radiation (2, 3 and 4 kGy) and storage time (10, 15 and 20 days) on the characteristics of pH, TVB, TBA and profile analysis of texture (hardness, chewiness, elasticity and cohesiveness) in headless shrimp peeled and stored at a temperature of (3±2 °C), with planning factorial of 22 full and 3 central points, totaling 7 tests. In the second step were selected the tests who maintained the best quality shrimp according to current legislation. Analyzes of moisture, protein, lipid, ash, water activity, instrumental color, cholesterol, fatty acid profile and microbiological analyzes (Staphylococcus coagulase positive (CFU/g); psychrotrophic aerobic (CFU/g) and Salmonella sp./25g) were performed. The results revealed a progressive decrease in the quality of the peeled shrimp (DCC) and headless (DCB) with the storage time, and irradiated samples maintained their quality with fifteen and twenty days of storage, while control samples have durability ten days. It was found that ionizing radiation did not influence the content of the shrimp studied (DCC and DCB). The cholesterol content presented next in all samples and the color remained of aspect of healthy shrimp. The main acid fatty saturated was palmitic (C16: 0), the monounsaturated featured was oleic acid (C18: 1 n-9) and the polyunsaturated was linoleic acid (C18: 2  6). Thus, can be detach the ionizing radiation as efficient in conserving the Litopenaeus vannamei, and that ensures the chemical composition of both types of maintenance of the physical and chemical composition of this food.